Metal organic frameworks (MOFs) as multifunctional nanoplatform for anticorrosion surfaces and coatings - Zhou, Chengliang; Pan, Mingfei; Li, Sijia; Sun, Yongxiang; Zhang, Hongjian; Luo, Xiaohu; Liu, Yali; Zeng, Hongbo (Advances in colloid and interface science, 2022)
Corrosion of metallic materials is a long-standing problem in many engineering fields. Various organic coatings have been widely applied in anticorrosion of metallic materials over the past decades. However, the protective performance of many organic coatings is limited due to the undesirable local failure of the coatings caused by micro-pores and cracks in the coating matrix. Recently, metal organic frameworks (MOFs)-based surfaces and coatings (MOFBSCs) have exhibited great potential in constructing protective materials on metallic substrates with efficient and durable anticorrosion performance. The tailorable porous structure, flexible composition, numerous active sites, and controllable release properties of MOFs make them an ideal platform for developing various protective functionalities, such as self-healing property, superhydrophobicity, and physical barrier against corrosion media. MOFs-based anticorrosion surfaces and coatings can be divided into two categories: the composite surfaces/coatings using MOFs-based passive/active nanofillers and the surfaces/coatings using MOFs as functional substrate support. In this work, the state-of-the-art fabrication strategies of the MOFBSCs are systematically reviewed. The anticorrosion mechanisms of MOFBSCs and functions of the MOFs in the coating matrix are discussed accordingly. Additionally, we highlight both traditional and emerging electrochemical techniques for probing protective performances and mechanisms of MOFBSCs. The remaining challenging issues and perspectives are also discussed. [Display omitted] •Recent advances of MOFs-based anticorrosion surfaces and coatings were reviewed.•Fabrication methods of MOFs-based anticorrosion surfaces/coatings were summarized.•Protective mechanisms of MOFBSCs and roles of MOFs were discussed.•Electrochemical techniques for characterizing MOFBSCs were introduced.•The remaining challenging issues and perspectives were discussed.